Is play therapy effective on young children with anxiety? - Mansor, Mariani; Lim, Yan Jun; Abdullah, Rohani; Madon, Zainal; Abu Samah, Asnarulkhadi; Lebai Nordin, Azizah (2012)
This paper examined to what extend does play therapy proved effective in treating children with anxiety symptoms. Prior to the intervention stage, 299 nursery school children from Pusat Anak PERMATA Negara (PAPN) were prescreened for anxiety symptoms, using the Caregiver-Teacher Report Form (CTRF). Pretest and analysis results based on teachers’ assessments revealed that 63 children aged between two to four years old showed anxiety symptoms in their behavior. From this sample, 33 children and 30 children were randomly assigned to control and experimental group. Post evaluation carried out after the play therapy intervention stage showed that teachers reported significant decline in anxiety level for children in the experimental group. Teachers’ reports showed significant decrease in anxiety level for children aged three in experimental group. Teachers also reported significant gender differences for children in experimental group and indicated that both males and females showed significant decrease in anxiety level. This study has further supported that play therapy is a developmentally appropriate intervention strategy in treating young children with anxiety symptoms.